Forms of Reflexivity and the Importance of Using them in Pedagogical Practice (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the fundamental improvement of the education system, it is necessary to carry out basic research in two directions, one of which is not less important than the other. The first direction covers all links of the education system and consists of retraining all pedagogical staff working in these links on the basis of special programs that provide for the organization of lesson processes with the introduction of modern pedagogical technologies and innovations. Experts who research pedagogical practices at all levels of our national education system should be involved in this direction. Consequently, this direction is a process that requires a lot of time and human resources. The second direction is the active involvement of young pedagogues who have received training based on a new approach to pedagogical practice. This direction includes research on ways to improve educational processes in higher and secondary special educational institutions, which are responsible for training pedagogic personnel for the lower and middle levels of education.